Exploring Barriers to Mental Health Services Utilization at Kabutare District Hospital of Rwanda: Perspectives From Patients - Muhorakeye, Oliviette; Biracyaza, Emmanuel (Frontiers in Psychology, 2021)
Barriers to mental health interventions remain the global public concern, but more obvious in low and middle income countries (LMICs). The barriers to accessibility include stigmatization, financial scarcity, poor accessibility and acceptability, poor awareness, poor affordability, sociocultural and religious influences, accessibility, and a weak health system. Although these mental diseases are the burdens that contribute to the global burden diseases, if we compare to other communicable and non-communicable diseases, we find that mental health is less prioritized at global, continental, and .local levels. Hence, this research aimed to investigate the barriers to the mental health services utilization at Kabutare District Hospital of the Southern Province in Rwanda. Qualitative study was carried out among the patients seeking health care at Kabutare District Hospital. Ten in-depth interviews with ten recruited patients seeking mental health services at the hospital were recruited. Interviews were audio-recorded and the notes were taken. Results indicated that lack of awareness, self and social stigma, and the socio-cultural beliefs were the fundamental barriers to the accessibility to the mental health interventions. It was revealed that poor accessibility, rural gossip networks, and social visibility within the communities compounded the stigma and social exclusion for the patients with the mental diseases. Among other factors that affect accessibility and acceptability to mental health therapies include social influences and traditional and religious beliefs and high cost for mental health interventions. Several barriers mainly stigma, shame and unawareness limit the patients to utilize mental health services. Community-based interventions need to be implemented for reducing the socio-cultural barriers mainly social stigma of patients with mental diseases in the medical settings.